Analysis of the risk factors of hospital mortality in patients with dilatational cardiomyopathy complicated by secondary insufficiency of atrioventricularvalves - R. Buriak (Ukrainian Journal of Cardiovascular Surgery, 2018)
Dilatational cardiomyopathy (DCM) is isolated chronic diffuse myocardial disease of unknown etiology, which occurs in the absence of changes in coronary arteries and is accompanied by cardiomegaly with expansion of the chambers of the heart with a decrease in the contractile function of its muscle and the development of symptoms of heart failure.The purpose of the work is to perform an analysis of the clinical characteristics of patients with DCM, which have an insufficiency of atrioventricular valves, to investigate the immediate results of their treatment.Materials and methods. The basis of the study was 142 patients with DCM with insufficiency of atrioventricular valves, who were on the examination and medical treatment at the Amosov Institute of Cardiovascular surgery from 01/01/2007 to 01/01/2014. The average age of patients was 49.8±14.5 years (9.0–74.0). The proportion of males and females was 106 (74.6%) and 36 (25.4%) respectively. All patients were symptomatic.The stage of CHF was evaluated as IIA in 30 (21.1%) patients, in ІІB – in 109 (76.8%) and ІІІ – in 3 (2.1%). Distribution of patients with functional New York Heart Association class (NYHA) were as follows: NYHA II – 30 (21.1%), NYHA III – 109 (76.8%), NYHA IV – 3 (2.1%) cases.According to data of transthoracic echocardiography, all patients had Mitral valve regurgitation (MR): moderate MR – in 122 (85.9%) cases, severe MR – 20 (14.1%) cases. Concomitant regurgitation on the tricuspid valve was registered in 137 (96.5%) cases, among them a small tricuspid valve regurgitation (TR) was in 44 (31.0%) cases, moderate – 71 (50.0%) cases and severe – 22 (15.5%) cases. The mean left ventricular ejection fraction (EF) was 27.5±6.3% (13–40). End-diastolic (EDI) and end-systolic (ESI) indices were 141.2±36.3 ml/m2 (75–258) and 101.8±31.9 ml/m2 (48–220), respectively. Pulmonary arterial pressure (PAP) was on average 50.6±9.8 mmHg (30–75), the presence of severe pulmonary hypertension (>50 mmHg) was detected in 60 (42.3%) cases.Hospital mortality was 3.5% for the group under study (5 deaths per 142 patients). The causes of death were: acute heart failure – 3 cases, acute respiratory failure, sepsis – 2 cases.In order to identify possible differences in quantitative clinical characteristics, as well as to determine their limit values, a comparative analysis of subgroups of survivors (n=137) and deceased (n=5) patients was performed. In the analysis of qualitative clinical characteristics, it was found that deceased patients significantly differed in the higher frequency of registration of cerebrovascular accident in history (p<0.000), acute heart failure (p<0.000), prevalence of patients with NYHA IV (p<0.000). At the level of the trend, there was a blockade of LBBB (p=0.068), mitral (p=0.090) and tricuspid (p=0.052) valves deficiencies.In addition, deceased patients significantly differed in the longer symptomatic period (p=0.050), with higher values of heart rate (p=0.050), systolic PAP which is reported on echocardiogram (p<0.000), systolic PAP which is measurements on right-sided cardiac catheterization (p<0.000), elevated leukocyte count (p<0.000), NT-proBNP (p<0.000), lactate (p<0.000), creatinine phosphokinase (p=0.004) and amylase (p<0.000). At the level of tendency, the value of total bilirubin (p=0,062).On the basis of the results for the one-factor analysis, the limit values for the following parameters were determined: heart rate 84 beats/min, systolic PAP which is reported on echocardiogram – 58 mmHg, systolic PAP which is measurements on right-sided cardiac catheterization – 50 mmHg. NT-proBNP levels – 4236 pg/ml, blood leukocytes – 9x109 cells/L, lactate – 2.2 mmol/L, blood alpha amylase – 57 mg/unit/ml, creatinine kinases – 188 U/L, total bilirubin – 30 μmol /L.As a result of one-factor analysis, the following range of characteristics were obtained which independently influence the result of surgical intervention: heart rate ≥84 beats/min (p=0.008), systolic PAP≥63 mmHg (p=0.001), systolic PAP which is measurements on right-sided cardiac catheterization ≥50 mmHg, leukocyte level≥9x109 cells/L, NT-proBNP ≥3000 pg/ ml (p<0.000), lactate ≥2.2 mmol/L (p=0.012), blood alpha amylase ≥57 mg/h/ml (p=0.001), creatinine phosphokinase ≥188 U/L and total bilirubin ≥30 μmol/L (p<0.000).The result of the study was the identification of prognostic risk factors for hospital mortality, which would differentiate the approach to substantiating the impressions for isolated medical treatment.Conclusions. The risk factors for hospital mortality in patients with DCM with atrioventricular valve insufficiency are heart rate ≥84 beats/min, systolic pulmonary arterial pressure ≥63 mmHg, systolic pulmonary arterial pressure which is measurements on right-sided cardiac catheterization ≥50 mmHg, leukocyte level ≥9x109 cells/L, NTproBNP ≥3000 pg/ ml, lactate level ≥2.2 mmol/L, blood α-amylase ≥57 mg/ml, creatinine kinase ≥188 U/L and total bilirubin ≥30 μmol/L.